From questionnaire to database: field work experience in the "Immigration, work and health survey" (ITSAL Project) De la encuesta a la base de datos: experiencia de trabajo de campo del estudio «Inmigración, trabajo y salud» (Proyecto ITSAL) - Carlos E. Delclos; Fernando G. Benavides; Ana M. García; María José López-Jacob; Elena Ronda (Elsevier, 2011)
Objective: Despite the need for information in the area of migration and health, the available data are sparse. We describe the field work in a cross-sectional study on the health of immigrant workers in Spain. Method: A convenience sample of workers from Colombia, Ecuador, Morocco and Rumania in four cities was targeted, using a block-walking approach. The outcome rates of the American Association of Public Opinion Research were estimated. Results: Of 6,504 persons approached, 71.4% were eligible contacts. Of these contacts, only 57.8% completed interviews. Response and cooperation rates were above 50%. Conclusions: Block-walking enabled surveyors to access difficult-to-reach groups. The use of specifically trained surveyors with a background similar to that of the target population increased the effectiveness of our methods. Objetivo: A pesar de la necesidad de información sobre salud de las poblaciones inmigrantes, los datos disponibles son escasos. El presente estudio describe el trabajo de campo en un estudio transversal sobre salud de los trabajadores inmigrantes en España. Método: Muestra de conveniencia de trabajadores procedentes de Colombia, Ecuador, Marruecos y Rumanía, por itinerarios, en cuatro ciudades. Se calcularon los indicadores de resultados propuestos por la American Association of Public Opinion Research. Resultados: Se accedió a 6504 personas, de las cuales el 71,4% cumplían criterios de inclusión, y de ellos sólo el 57,8% completó la entrevista. Las tasas de respuesta y cooperación superaron el 50%. Conclusiones: La estrategia de muestreo por itinerarios ha permitido a los encuestadores acceder a esta población. También ha sido beneficiosa la participación de encuestadores especialmente formados y con un perfil similar al de la población objetivo.